STRATEGI DIGITALISASI LAYANAN PERBANKAN DALAM RANGKA PEMULIHAN DAN PENINGKATAN KINERJA BANK PASCA PANDEMI COVID-19 - I Gusti Ngurah Satria Wijaya; Pande Putu Yudiastra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
The Covid-19 pandemic has not only had an adverse impact on human health, it has also had an adverse effect on the economic sectors/sectors in Indonesia, especially in the banking sector. Commercial Banks in operating their duties as financial organizations/institutions are required to be able to relate to many people. However, from a different perspective, the challenges and dangers of corona virus infection are the main source of problems that weaken this sector. Likewise, during the post-Covid-19 pandemic, the banking sector was required to make policies to recover from the decline in performance due to the Covid-19 pandemic. This study aims to carry out an analysis of banking service digitization strategies in the context of recovering and improving bank performance after the Covid-19 pandemic. This study takes research subjects from the management of commercial banks that have used digital technology in Bali. The technique used in this study is a qualitative method/or technique. The results of his research are digitalization strategies used by commercial banks in recovering and improving performance in the post-pandemic period, namely digital transformation strategies, commercial bank fintech product innovation strategies, bank collaboration strategies with fintech service providers, and collaboration strategies with institutions/institutions. The results can provide recommendations for the management of commercial banks to adopt a policy to improve banking performance after the Covid-19 pandemic